JNE’s Cross-Media Communication Strategy to Strengthen the “Connecting Happiness” Brand Narrative - Siska Ramadhani; Aryo Subarkah Eddyono (CV. Publikasi Indonesia, 2026)
This study examines JNE's cross-media communication strategy in delivering the